TMS Enhances Retention of a Motor Skill in Parkinson's Disease - Moisello, Clara; Blanco, Daniella; Fontanesi, Cecilia; Lin, Jing; Biagioni, Milton; Kumar, Pawan; Brys, Miroslaw; Loggini, Andrea; Marinelli, Lucio; Abbruzzese, Giovanni; Quartarone, Angelo; Tononi, Giulio; et al. (Brain stimulation, 2015)
In Parkinson's disease (PD), skill retention is poor, even when acquisition rate is generally preserved. Recent work in normal subjects suggests that 5 Hz-repetitive transcranial magnetic stimulation (5Hz-rTMS) may induce phenomena of long-term potentiation at the cortical level. We thus verified whether, in PD, 5Hz-rTMS enhances retention of a visuo-motor skill that involves the activity of the right posterior parietal cortex. A group of patients with PD was tested in two two-day sessions, separated by one week (treatment and placebo sessions). The first day of each session, they learned to adapt their movements to a step-wise 60° visual rotation. Immediately after the task, either real 5Hz-rTMS (treatment) or sham (placebo) stimulation was applied over the right posterior parietal cortex (P6). Retention of this motor skill was tested the following day. In patients with PD, adaptation achieved at the end of training was comparable in the treatment and placebo sessions and was similar to that of a group of age-matched controls. However, retention indices tested on the following day were significantly lower in the placebo compared to the treatment session in which retention indices were restored to the level of the controls. Importantly, reaction and movement time as well as other kinematic measures were the same in the treatment and placebo sessions. These results suggest that rTMS applied after the acquisition of a motor skill over specific areas involved in this process might enhance skill retention in PD. •Retention of a visuo-motor skill is impaired in PD.•Retention in PD improves after rTMS to the right parietal cortex.•rTMS to the right posterior parietal cortex does not affect kinematics.